Pengaruh Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention Karyawan Melalui Komitmen Afektif - Dewi Rosalina; Harun Al Rasyid; Dwiyani Sudaryanti (Jurnal Minfo Polgan, 2026)
Employee turnover is a fairly common phenomenon and a major challenge for companies, including the Jabung Syariah Agro Niaga Producers Cooperative. High turnover can lead to decreased productivity, increased recruitment costs, and disrupted company operations. Therefore, it is important to understand the factors that contribute to employee turnover. Turnover decisions begin with turnover intention. This study aims to analyze the influence of Job Satisfaction on affective commitment, analyze the influence of Job Stress on affective commitment, analyze the influence of Job Satisfaction on Turnover intention, analyze the influence of Job Stress on Turnover intention, analyze the influence of Affective Commitment on Turnover intention, analyze the influence of Affective role as a mediator of the influence of Job Satisfaction on Turnover intention, and analyze the influence of Affective Commitment as a mediator of the influence of Job Stress on Turnover intention. This study involved 155 respondents as a sample, with data analysis using SmartPLS. The test results showed that job satisfaction has a positive and significant influence on affective commitment, while job stress has a negative and significant influence on affective commitment. In addition, job satisfaction was proven to have a negative and significant influence on turnover intention, while job stress had a positive and significant influence on turnover intention. Affective commitment was also found to have a negative and significant influence on turnover intention. Furthermore, job satisfaction and job stress were found to have an indirect influence on turnover intention through affective commitment as a mediating variable.